Peningkatan Kesejahteraan Santri Berbasis Manajemen Pengelolaan Wakaf Produktif di Pesantren Assyifa Subang - Muhammad Hamdan Ainulyaqin; Listian Indriyani Achmad; Meysi Asrol Meilani (ITB AAS INDONESIA Surakarta, 2023)
This study aims to determine the management of waqf management carried out at the Assyifa Islamic Boarding School and to analyze the productive waqf management strategy in an effort to improve the welfare of the students at the Assyifa Islamic Boarding School. This research is a field research, with a descriptive qualitative research type whose explanation uses a description of the problem being studied. Data collection techniques by means of observation, interviews, and documentation. The data analysis technique used is to carry out the stages of data collection, data reduction, data presentation, and examination of research conclusions. The results of this study indicate that the management of productive waqf management at the Assyifa Islamic Boarding School resulted in good development, many changes were produced after the management of productive waqf. Management and development of productive waqf is still not optimal, among others, caused by nadzir who is less competent in managing and less capable in managing productive waqf. The management of productive waqf management is still not managed optimally, so it has not given a prominent effect that is so pronounced in the changes in improving the welfare of students.